Impact of COVID‐19 pandemic on mental health of patients with inherited bleeding disorders in Germany. Issue 6 (15th September 2020) - von Mackensen, Sylvia; Halimeh, Susan; Siebert, Manuela; Wermes, Cornelia; Hassenpflug, Wolf; Holstein, Katharina; Olivieri, Martin
Abstract: Background: The worldwide pandemic spread of SARS‐CoV‐2 can lead to either respiratory infection or containment‐associated isolation with possible higher impact on chronic diseases such as inherited bleeding disorders (IBD). The aim of the study was to evaluate the impact of COVID‐19 on patients and caregivers of IBD patients regarding their concerns and worries related to own health, access to treatment and availability of factor concentrates and their experiences related to medical care. Methods: Multicentre, cross‐sectional study evaluating the impact of COVID‐19 on mental health of IBD patients. An ad hoc questionnaire was developed and sent to 586 patients/caregivers with haemophilia A, haemophilia B and VWD type III. The survey included information on demographic and clinical data, needs, concerns and experiences regarding medical care during COVID‐19 pandemic. Results: In total, 355 of the IBD‐Group (200 patients, 155 caregivers) completed the survey (61.7% response rate). Most patients suffered from haemophilia A (73.8%) and were severely affected (64.7%). Eleven patients were in quarantine due to suspected COVID‐19; none had symptoms. One quarter worried (very) strongly about getting the coronavirus, 71.3% asked themselves what will happen to them when they will get COVID‐19, 40.1% felt unchanged, and 18.9% worried about delivery difficulties of their IBD treatment product. In 52.8%, medical appointments were postponed. Significant differences between caregivers and patients were found in most aspects. Discussion: The IBD patients affected by a chronic disorder have particular thoughts and worries regarding COVID‐19. Haemophilia specialists should be committed to address these concerns and guarantee treatment despite containment strategies.